PENDIDIKAN HOLISTIK, PENGEMBANGAN KURIKULUM DAN EVALUASI PENDIDIKAN - Fadjar Adji Nuryanto; Kholid Mawardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Miller, describes three basic principles of holistic education: connectedness, inclusion, and balance. Connectedness refers to a shift from a fragmented approach to curriculum to one that seeks to facilitate connections at every level of learning. Some of these connections include integrating analytical and intuitive thinking, connecting the body and mind, integrating subjects, connecting to the community, providing a link to the earth, and connecting to the soul and spirit. The theory of